A worldwide survey on the use of animal‐derived materials and reagents in scientific experimentation. Issue 9 (18th July 2022) - Cassotta, Manuela; Bartnicka, Joanna Julia; Pistollato, Francesca; Parvatam, Surat; Weber, Tilo; D'Alessandro, Vito; Bastos, Luisa Ferreira; Coecke, Sandra
Abstract: The use of cell and tissue‐based methods in basic, applied and regulatory science has been increasing exponentially. Animal‐derived components, including serum, coating materials, growth factors and antibodies are routinely used in cell/tissue cultures and in general laboratory practices. In addition to ethical issues, the use and production of animal‐derived materials and reagents raises many scientific concerns, generally associated with presence of undefined components and batch‐to‐batch variability, which may compromise experimental reproducibility. On the other hand, non‐animal materials and reagents, such as human cells, alternatives to animal sera or non‐animal recombinant antibodies, are becoming increasingly available, and their use is encouraged by the EU Directive 2010/63 and the Guidance Document on Good In vitro Method Practices (GIVIMP), published by the Organization for Economic Cooperation and Development (OECD). In an effort to map the current state of use of animal‐derived reagents across different sectors and to identify the obstacles possibly hampering the implementation of non‐animal derived alternatives, a global online survey addressed to scientists working on in vivo, in vitro, in silico methods, in academia as well as pharmaceutical or cosmetic companies, was conducted with the goal to understand: 1) the most commonly used animal‐derived materials and reagents, 2) the main issues associated with the production and use of animal‐derived materials and reagents, 3) the current level of knowledge on available non‐animal alternative materials and reagents, and 4) what educational and information sources could be most useful or impactful to disseminate knowledge on non‐animal alternatives. This paper provides an overview of the survey replies and discusses possible proposals to increase awareness, acceptance and use of non‐animal ingredients.